Motivasi Kerja Pada Perempuan Bali Yang Sudah Menikah Dalam Perspektif Work-Life Balance - Ni Wayan Sinthia Widiastuti; I Gusti Ngurah Putra Suryanata (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTWomen who have married initially only played a role in the domestic sector, which is focused on the nature of women biologically, namely taking care of the household. Current development through the influence of globalization and meeting the need to encourage women to play a role in the public sector. Especially in Bali, which is very thick with their culture tradition when a woman takes on the role as a breadwinner, as a housewife, and active in society, so that Balinese women play three roles. The purpose of the research is to explain the work motivation of Balinese women who work in a work-life balance perspective. This study used a qualitative method with a phenomenological approach. The sampling technique used was purposive sampling technique. Informants in this study consisted of seven people including four people working in the informal sector and three people working in the formal sector, with the criteria of women, ethnic Balinese, Hindus, married, having children, working. The technique of data collection is done by semi-structured interviews. This research shows a picture of married Balinese women in maintaining balance or often referred to as work-life balance and encouragement that makes Balinese women decide to work, even though they know many roles that are carried out.